Les modalités et les caractéristqiues du processus d’adaptation de l’industriel canadienne à la concurrence internationale - Robert, Patrick (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1983)
The developing countries' inroads into the traditional strongholds of the developed countries are seen by some industrialized countries as a threat. In any event, the situation is forcing them to make structural adjustments, with the inherent costs this imposes on business and labour.The primary goal of this article is to determine whether these changes threaten to « deindustrialize » Canada. Using an analysis of Canadian industry's trade performance in 150 categories and sub-categories of manufactured goods, the author concludes that Canadian business is indeed adapting to greater international competition and that the threat of deindustrialization has not yet materialized.The article's second objective is to discover the process by which this adjustment occurs. Concerning the business sector, the author found that businesses have adjusted to these changes primarily through a decline in the number of new firms or new plants, rather than through an increase in the number of closures.For labour, the results of a specially developed survey tend to indicate that the adjustment process also is not quite as harsh as might normally be expected. The author therefore sees little likelihood of major upheavals or massive worker displacement. He cautions, however, that we are still faced with transitional problems whose potential impact should not be underestimated.